Cultural psychology - Heine, Steven J. (Laura Ann); 1906-1998. 1947- (Sandra M.); (Margaret M.) (New York, NY W.W. Norton, 2012)
An introduction to cultural psychology -- Culture and human nature -- Cultural evolution -- Methods for studying culture and psychology -- Development and socialization -- Self and personality -- Motivation -- Cognition and perception -- Interpersonal attraction, close relationships, and groups -- Living in multicultural worlds -- Physical health -- Mental health -- Morality, religion, and justice -- Emotions -- Glossary G-1 -- References R-1 -- Credits C-1 -- Name index N-1 -- Subject index S-1.
Includes bibliographical references and index.
Keywords: Ethnopsychology; Tâm lý học